Use of an on/of tetracycline riboswitch to control protein production in Komagataella phafi - Vieira, Igor Patrick Vasconcelos (2023)
The methylotrophic yeast Komagataella phafi is one of the most important microbial platforms to produce recom binant proteins. Despite its importance in the context of industrial biotechnology, the use of synthetic biology approaches in K. phafi is hampered by the fact that few genetic tools are available for precise control of gene expres sion in this system. In this work, we used an RNA aptamer activated by tetracycline to modulate protein production at the translational level. Using lacZ as gene reporter, we have demonstrated signifcant reduction of the heterolo gous protein upon addition of tetracycline. Furthermore, this genetic control device was applied for the control of Ku70p. This protein is involved in non-homologous recombination and the control of its production paves the way for the development of strains exhibiting higher rates of homologous recombination.